2007
DOI: 10.1590/s1516-89132007000600025
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m-labeled stealth pH-sensitive liposomes: a new strategy to identify infection in experimental model

Abstract: The diagnosis of inflammatory and infectious processes is an important goal in medicine. The use of radiopharmaceuticals for identification of inflammation and infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Recently, Iman and colleagues ( 27 ) also investigated the distribution of LAmB and DAmB in L. major -infected BALB/c mice, but skin was not evaluated in this study. Increased accumulation of liposomes in inflammatory over healthy sites has also been described for subcutaneous tumors ( 28 ), bacterial skin abscesses ( 29 , 30 ), and fungal infections ( 31 ). The so-called enhanced permeation and retention effect, increased drug accumulation at sites of leaky vasculature and defective lymphatic drainage, has been coined as the rationale behind nanoparticle-based drug delivery in cancer and inflammation ( 16 ).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Iman and colleagues ( 27 ) also investigated the distribution of LAmB and DAmB in L. major -infected BALB/c mice, but skin was not evaluated in this study. Increased accumulation of liposomes in inflammatory over healthy sites has also been described for subcutaneous tumors ( 28 ), bacterial skin abscesses ( 29 , 30 ), and fungal infections ( 31 ). The so-called enhanced permeation and retention effect, increased drug accumulation at sites of leaky vasculature and defective lymphatic drainage, has been coined as the rationale behind nanoparticle-based drug delivery in cancer and inflammation ( 16 ).…”
Section: Discussionmentioning
confidence: 90%
“…These drug-delivery systems have proven to be interesting carriers of imaging agents to identify infectious sites, since these areas have high blood flow and permeability that allow for the liposomes to extravasate and accumulate. [13][14][15] Despite that, radiolabeled liposomes are not able to differentiate septic from aseptic inflammation. In an effort to overcome the lack of specificity of radiolabeled liposomes and to improve the image quality, our research group has previously developed pH-sensitive liposomes containing 99m technetium-radiolabeled CFT ( 99m Tc-CFT) for the diagnosis of bone infections.…”
mentioning
confidence: 99%
“…However, Tc-99 m radiolabeled PC:SDC micelles can also be assumed as sensitive radiopharmaceutical agents due to the mechanism of imaging of infection and inflammation. 99m Tcradiolabeled, PEGylated, PC, SDC and DTPA-PE containing nanosized micelles can accumulate at infection and inflammation sites due to long vascular circulation of vesicles by small particle size and surface coating by an hydrophilic polymer (such as PEG) [47,[52][53][54]. It was reported in some previous studies that the accumulation of radiolabeled liposomes in at infectious sites is performed by leakage of the vesicles through vessels.…”
Section: In Vitro Bacterial Bindingmentioning
confidence: 99%
“…This leakage depends on the enhanced vascular permeability and following phagocythosis by macrophages of infected tissue. It was reported that the endothelial junctions existing in the blood vessel provides the penetration of the particles smaller than 200 nm from the vascularization [48,54]. Therefore, surface coated, nanosized drug delivery systems like liposomes can be accumulated at the site of infection and inflammation due to long circulation, enhanced vascular permeability and reduced removal by opsonisation [49,52,65].…”
Section: In Vitro Bacterial Bindingmentioning
confidence: 99%
See 1 more Smart Citation